The Church as Christ"s broken body responding to the emerging global challenges in a divided world - Hewitt, Roderick R. (HTS teologiese studies, 2017)
Public debate about the role of the church within society has gained momentum especially because the contemporary changing global political and economic landscape has resulted in deeply a divided world. People are asking questions about the missional identity and vocation of the church. If the church is the broken body of Christ in the world, what are the ways in which it is expressing that brokenness in practical ways? This vulnerable status necessitates modelling the politics of Jesus that risks putting up resistance against all threats that prevent people from experiencing fullness of life. The contemporary era of global governance is characterised by ‘moral lowlifes’ in political leadership that uses judicial and executive overreach to weaken democracy and empower the wealthy elites. Furthermore, the impact of technology and computation on shaping human relations has produced a consequential decline in human trust and relationships. Therefore, the missional agenda of the church as the broken body of Christ serving a divided world, calls for building life-affirming relationships that overcome dehumanising barriers.